2013
DOI: 10.1086/669606
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Symbionts as Manipulators of Plant Reproductive Biology

Abstract: Dryad data: http://dx.doi.org/10.5061/dryad.84c26.abstract: Symbioses have shaped the evolution of life, most notably through the fixation of heritable symbionts into organelles. The inheritance of symbionts promotes mutualism and fixation by coupling partner fitness. However, conflicts arise if symbionts are transmitted through only one sex and can shift host resources toward the sex through which they propagate. Such reproductive manipulators have been documented in animals with separate sexes but not in oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 57 publications
1
17
0
Order By: Relevance
“…Although fungal endophytes are commonly considered defensive mutualists, Gorischek et al (2013) observed that hermaphrodites infected with fungal symbionts had female-biased sex allocation; this is in contrast to the male-biased allocation pattern observed in non-endophyte-infected conspecific individuals obtained through segregation (imperfect maternal inheritance). They also showed greater vegetative propagation, again permitting symbiont maintenance.…”
Section: Deviations In Sex Allocation In Hermaphrodite Plantsmentioning
confidence: 75%
See 1 more Smart Citation
“…Although fungal endophytes are commonly considered defensive mutualists, Gorischek et al (2013) observed that hermaphrodites infected with fungal symbionts had female-biased sex allocation; this is in contrast to the male-biased allocation pattern observed in non-endophyte-infected conspecific individuals obtained through segregation (imperfect maternal inheritance). They also showed greater vegetative propagation, again permitting symbiont maintenance.…”
Section: Deviations In Sex Allocation In Hermaphrodite Plantsmentioning
confidence: 75%
“…"Reproductive parasitic" behaviors in plants are commonly associated with mutations in the mitochondrial genome, but have recently also been ascribed to heritable fungi (Gorischek et al 2013). Reproductive parasitism in animals is associated with a wide variety of microbial symbionts: viruses, bacteria, unicellular eukaryotes, and fungi that pass from a female to her progeny either inside eggs or through smearing on the outside of eggs followed by trophic acquisition (Terry et al 2004;Nakanishi et al 2008;Duron and Hurst 2013;Gorischek et al 2013). Although many heritable microbes are simply "beneficial symbionts," reproductive parasitism of the type described above is widespread (and may be combined with beneficial impacts on the female host).…”
mentioning
confidence: 99%
“…They provide numerous benefits to plants, including deterring herbivory by producing toxic secondary metabolites (Clay, 1988) and enhancing drought tolerance (Kane, 2011) and nutrient uptake (Malinowski, Alloush, & Belesky, 2000). These effects have important consequences for host plants and their communities; for example, they can bias sex allocation (Gorischek et al, 2013), facilitate host range expansion (Afkhami, McIntyre, & Strauss, 2014), suppress forest succession (Rudgers et al, 2007), negate productivity-diversity relationships (Rudgers, Koslow, & Clay, 2004), and alter plant, herbivore, predator, and decomposer community compositions (Lemons, Clay, & Rudgers, 2005;Finkes et al, 2006;Afkhami & Strauss, 2016).…”
Section: (1) Endophytesmentioning
confidence: 99%
“…, Faeth , , Gorischek et al. ). In contrast, studies of nonsystemic fungal symbionts, although fewer in number, show potentially important but highly variable effects on plant fitness and thus their ecological significance is less well understood (Rodriguez et al.…”
Section: Introductionmentioning
confidence: 99%